Interjections in American and Danish courtroom interaction: A linguistic and legal cultural comparison - Mortensen, Sune Sønderberg (Scandinavian Studies in Language, 2019)
This study compares the use of interjections by the defence lawyers in an American and a Danish criminal trial during their direct-examination of their clients, i.e. the defendants. Through quantitative and qualitative analyses it is shown that the Danish lawyer uses interjections much more frequently than the American lawyer, and that the interjections used by the American lawyer tend to have different interactional functions than those used by the Danish lawyer. Thus, while the American lawyer practices a composed and transactional style of interaction, the Danish lawyer adopts a fairly loose and casual style. The interactional styles of the two lawyers, as seen through their use of interjections, are discussed and explained as reflections of central cultural traits of the two countries’ legal traditions, drawing, amongst others, on the basic divide between common law adversarialism and civil law inquisitorialism.